Friends in Low Places: Responses of a Benthic Stream Fish to Intra‐Prey‐Guild Alarm Cues. (13th October 2016) - Anderson, Kelsey A.; Mathis, Alicia
Abstract: Many aquatic species produce chemical alarm cues that serve as a warning to nearby conspecifics. In mixed‐species aggregations, individuals may also benefit by 'eavesdropping' on the chemical alarm cues of other species that are in the same prey guild. Rainbow Darters ( Etheostoma caeruleum ) are benthic fish that co‐occur with native Ozark Minnows ( Notropis nubilus ), recently introduced Western Mosquitofish ( Gambusia affinis ), and native Oklahoma Salamanders ( Eurycea tyrnerensis ), all of whom are vulnerable to the same predators. We tested the responses of darters to the damage‐released alarm cues of conspecifics (positive control), minnows, and mosquitofish; alarm cues from Bumblebee Gobies ( Brachygobius doriae ) served as a negative (allopatric) control. We also tested the response of sympatric and allopatric darters to the damage‐released alarm cues of Oklahoma Salamander. Darters exhibited a fright response to conspecific and minnow alarm cues, but not to cues from mosquitofish or gobies. Lack of response to mosquitofish cues could be because they are introduced or because they typically occur higher in the water column than darters. Darters that were sympatric with the salamander exhibited a fright response to the alarm cues of the salamander, while allopatric darters did not. Rainbow Darters can develop responses to the alarm cues of syntopic species (minnows and Oklahoma Salamander) within their prey guild.